Rectal prolapse in children: Laparoscopic suture rectopexy is a suitable alternative - Puri Bipin (Wolters Kluwer Medknow Publications, 2010)
Aim : To study the clinical outcome of laparoscopic suture rectopexy (LSRP) in children with persistent rectal prolapse (PRP). Materials and Methods : Nineteen cases of PRP were managed with LSRP from February 2005 to August 2009. Results : All were followed up for an average duration of 6 months. Only one child had recurrence and was managed with sclerotherapy. Conclusion : LSRP is safe, feasible in children and gives satisfactory results.